The Teaching Materials of Youth Novels Loaded with Moral Values for High School - Evi Supriatin; Rizal Ibrahim Aji; Suherli Kusmana (Ikaprobsi, 2023)
This study aims to address the problem of the quality of Indonesian language learning. The problem in question is the availability of novel text teaching materials in both printed and online Indonesian language textbooks. Digital teaching materials can streamline learning and students are not mistaken in interpreting the moral values ​​of a novel. This research uses research and development methods. Based on the study of novel text learning carried out, it is known that teachers need teaching materials that can overcome the teacher's difficulties in showing examples that are easily accessible to students. From the study of youth novels, the novel